The influence of intersectional identities on the employment integration of Sub-Saharan African women immigrants in the U.S. Issue 1 (2nd January 2020) - Ngoubene-Atioky, Arlette J.; Lu, Christopher; Muse, Chantal; Tokplo, Laetitia
Abstract: Using a triangulation theoretical framework, this study investigated the influence of self-reported social identities on employability and the impact of employment on the well-being of sub-Saharan African women immigrants (SSAWI). Regression analyses revealed that parenting role influenced the work status of SSAWI. At first, unemployment was found to predict a greater sense of well-being in SSAWI mothers and employment increased the well-being of child-free SSAWI with less than a postsecondary education. Years later, SSAWI who served in a parenting role were more likely to be employed, and employment status significantly predicted greater well-being in SSAWI. Culture-centered implications and limitations of the study are provided.